Circus days under the big top. - Glendinning, Richard; Colabella, Vincent (Champaign, Ill., Garrard Pub. Co., 1969)
Traces the history of the circus from the Roman Circus Maximus to modern shows in covered arenas, with emphasis on the circus people's way of life during the Golden Age of the Big Top.
13
Keywords: Circus; Circus -- Juvenile literature